334 Differences in risk factors for neurophysiologically confirmed carpal tunnel syndrome and illness with similar symptoms but normal median nerve function. (11th October 2013) - Coggon, D; Ntani, G; Harris, E C; Linaker, C; Van der Star, R; Cooper, C; Palmer, K T
Abstract : Objectives: To explore whether neurophysiologically confirmed carpal tunnel syndrome (CTS) has different risk factors from sensory symptoms in the hand that occur in the absence of impaired median nerve conduction. Methods: We compared 475 patients with neurophysiologically confirmed (NP+ve) CTS, 409 patients investigated for CTS but negative on neurophysiological testing (NP-ve), and 799 controls. Exposures to risk factors were ascertained by self-administered questionnaire. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were estimated by logistic regression. Results: NP+ve CTS was associated with obesity, use of vibratory tools, repetitive movement of the wrist or fingers, poor mental health and workplace psychosocial stressors. NP-ve illness was also related to poor mental health and occupational psychosocial stressors, but differed from NP+ve disease in showing associations also with prolonged use of computer keyboards and tendency to somatise, and no relation to obesity. In direct comparison of NP+ve relative to NP-ve cases, the most notable differences were for obesity (OR 2.7, 95% CI 1.9–3.9), somatising tendency (OR 0.6, 95% CI 0.4–0.9), diabetes (OR 1.6, 95% CI 0.9–3.1) and work with vibratory tools (OR 1.4, 95% CI 0.9–2.2). Conclusions: When viewed in the context of earlier research, our findings suggest that obesity, diabetes, use of hand-held vibratory tools, and repeated forceful movements of the wrist and hand are causes of impaired median nerve function. In addition, sensory symptoms in the hand, whether from identifiable pathology or non-specific in origin, may be rendered more prominent and distressing by hand activity, low mood, tendency to somatise, and psychosocial stressors at work.